Man on a mission : James Meredith and the battle of Ole Miss - Goudsouzian, Aram (The University of Arkansas Press, 2022)
"In 1962, James Meredith famously desegregated the University of Mississippi. Drawing upon historical research and creative inspiration, this graphic history depicts the civil rights icon's relentless pursuit of justice"--